Reducing random measurement error in assessing postural load on the back in epidemiologic surveys - Burdorf, Alex (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'The goal of this study was to design strategies to assess postural load on the back in occupational epidemiology by taking into account the reliability of measurement methods and the variability of exposure among the workers under study.' ' METHODS ': 'Intermethod reliability studies were evaluated to estimate the systematic bias (accuracy) and random measurement error (precision) of various methods to assess postural load on the back. Intramethod reliability studies were reviewed to estimate random variability of back load over time.' ' RESULTS ': 'Intermethod surveys have shown that questionnaires have a moderate reliability for gross activities such as sitting, whereas duration of trunk flexion and rotation should be assessed by observation methods or inclinometers. Intramethod surveys indicate that exposure variability can markedly affect the reliability of estimates of back load if the estimates are based upon a single measurement over a certain time period. Equations have been presented to evaluate various study designs according to the reliability of the measurement method, the optimum allocation of the number of repeated measurements per subject, and the number of subjects in the study.' ' CONCLUSION ': 'Prior to a large epidemiologic study, an exposure-oriented survey should be conducted to evaluate the performance of measurement instruments and to estimate sources of variability for back load. The strategy for assessing back load can be optimized by balancing the number of workers under study and the number of repeated measurements per worker.
Keywords: bias; epidemiology; physical load; reliability